Proteomic Insights into citT-Deletion Induced Metabolic Sensitivity in Bio-Degumming of Ramie Fibers by Bacillus subtilis - Qi Yang; Yuqin Hu; Xiangyuan Feng; Guoguo Xi; Ke Zheng; Zhenghong Peng; Fengbo Han; Lifeng Cheng; Shengwen Duan (Journal of Natural Fibers)
Cellulose fibers from ramie is a kind of functional biological material with multipurpose in the textile industry, which called as “China grass.” The degumming of ramie fibers performed with Bacillus subtilis were regulated by response regulator CitT from CitS/CitT two-component system through specifically functioning on the degradation of component pectin. In this study, comparative proteomic analysis was executed to obtain insights into the sensitivity by which the metabolic network induced by the absence of CitT protein, and to further explore the regulatory mechanism during bio-degumming process of ramie fibers. Results showed that 29 differentially expressed proteins were detected from original strain and mutant strain, which were mainly involved in transmembrane transport system, two-component system, and amino acid metabolism. This study demonstrated that the lack of CitT protein could result in the down-regulation of enzymes in histidine biosynthesis pathway, and the up-regulation of enzyme in arginine degradation pathway. This study is the first time to reveal comprehensive information about the regulatory function of CitT protein in bio-degumming of ramie fibers, and may provide important scientific and technological basis for targeted constructing engineering strains in degumming of ramie fibers.